Differences in the Dynamics of Academic Emotions for New Students and Pre-service Teacher Professional Education (PPG) Students - Akhmad Harum (Universitas PGRI SUMATERA BARAT, 2023)
This study aims to determine the differences in the dynamics of academic emotions of new students and prospective teacher professional education (PPG) students in the Guidance and Counseling study program at Makassar State University as seen from gender and culture. This research is qualitative with a case study model using the purposive sampling technique to determine research subjects. The research subjects consisted of five freshmen from the class of 2022 and five pre-service PPG students in the field of guidance and counseling studies who had differences in gender and culture. Data collection methods are observation, in-depth interviews, and journal writing at the beginning and end of the semester. The data analysis technique uses a conventional model, namely thematic analysis techniques, with steps such as condensation, data presentation, and conclusion drawing. The results of this study indicate that new students and pre-service teacher professional education (PPG) students have differences in negative and positive emotions, namely new students, negative emotions experienced feel anxious about the results achieved, sad and depressed when at the beginning of the semester because they are just adapting to the environment and this happens to all male and female students and positive emotions for new students in the aspects of gender and culture are generally the same, namely in the form of being happy to have friends with different cultural backgrounds and happy when the task is completed and collected properly and. In PPG Pre-service students, the negative emotions experienced by male and female students are the same, namely feeling afraid of the demands of the tasks on the LMS, being bored with the many tasks and worrying about not being able to complete the tasks and processes that will be undertaken for a year with a pattern that he thinks is quite challenging seeing from PPG Pre-service Class 1 and feeling that the negative emotions experienced have nothing to do with the cultural factors they embrace. In building positive emotions, new students and Pre-Service PPG are generally the same in addition to a sense of liking the course but also the existence of motivation or encouragement such as role models, religious goals, a sense of wanting to make parents proud, seeing the success of others, the desire not to be easily fooled, and having ideals and hopes for both oneself and parents.